Efek Mie Pisang dan Sukun terhadap Glukosa Darah Sewaktu - Nursalam Nursalam; Rista Fauziningtyas; Candra Panji Asmoro; Kusnanto Kusnanto; Merryana Adriani (Jurnal Ners, 2016)
Introduction: Public awareness of healthy lifestyles cause a change in the selection of foodstuffs for consumption. Bananas and breadfruit flour additions increase the fiber content on the noodles. The purpose of this study was to determine the composition of noodles flour substitute on the effect on an increase in the lowest Glucose levels. Methods: The research design was pretest posttest control group design. Sample obtained as many as 58 students of the Faculty of Nursing University of Airlangga who meet the inclusion and exclusion criteria. 58 samples were divided into three groups, namely Noodles A (control), B (substitution 30%) and C (substitution 20%). Glucose levels examination carried out before eating noodles and 60 minutes after eat it. The data analysis of this study was the one-way ANOVA. Results: Based on the one-way ANOVA test was obtained p = 0.000 (p <0.050), which means no differences in outcomes in all three groups. The highest increasing of glucose levels is group A and the lowest in group B. Discussion: The addition of banana and breadfruit flour on the noodles can reduce the increase in the glucose levels after eat it. Further research needs to be done to determine the content of noodles with a banana and breadfruit flour and glucose’s responses in patients with diabetic mellitus.